1992
DOI: 10.1111/j.1600-0773.1992.tb00440.x
|View full text |Cite
|
Sign up to set email alerts
|

Adipose Tissue Distribution and Chemical Structure of Basic Lipophilic Drugs: Desipramine, N‐Acetyl Desipramine, and Haloperidol

Abstract: Single-dose intravenous injections of desipramine to rats resulted in a distribution pattern typical of basic lipophilic drugs, i.e., highest concentrations in lung and lowest in adipose tissue and plasma. In contrast, after N-acetyldesipramine, a non-basic analogue of desipramine with comparable lipophilicity, concentrations of this drug in adipose tissue were much higher than in lean tissue or plasma as a result of redistribution into the former and rapid disappearance from the latter tissue. N-Acetyldesipra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 7 publications
(7 reference statements)
0
9
0
Order By: Relevance
“…Interestingly, when the basic nitrogen of desipramine was acetylated to reduce basicity (and therefore, propensity to accumulate in lysosomes) the distribution of the drug now favored adipose tissue and the overall half‐life of the derivative was reduced relative to the basic parent compound, despite the fact that the derivative had similar lipophilicity to the parent compound. This work exemplifies the importance of lysosomal sequestration of amines in organ distribution, volume of distribution, and clearance parameters 65…”
Section: Therapeutic Implications/applications Of Lysosomal Sequestramentioning
confidence: 75%
“…Interestingly, when the basic nitrogen of desipramine was acetylated to reduce basicity (and therefore, propensity to accumulate in lysosomes) the distribution of the drug now favored adipose tissue and the overall half‐life of the derivative was reduced relative to the basic parent compound, despite the fact that the derivative had similar lipophilicity to the parent compound. This work exemplifies the importance of lysosomal sequestration of amines in organ distribution, volume of distribution, and clearance parameters 65…”
Section: Therapeutic Implications/applications Of Lysosomal Sequestramentioning
confidence: 75%
“…For instance, in the study with mice [21], it was shown that a derivative of AQ with greater basicity displayed a longer residence time in tissues. In another study with rats, it was shown that N-acetyldesipramine, a non-basic analogue of desipramine, had lower tissue and plasma half-lives [20]. Therefore, even though AQ is rapidly metabolized to DAQ in vivo, the tissue accumulation seen in vitro with the parent compound may be similar to tissue accumulation of DAQ in vivo.…”
Section: Uptake Of Aq Across the Caco-2 Cell Apical Membranementioning
confidence: 97%
“…It has been suggested that basic lipophilic compounds are retained in acidic lysosomes of lean tissues rather than in adipose tissue and plasma [20]. Interestingly, in a study whereby mice received a single i.p.…”
Section: Uptake Of Aq Across the Caco-2 Cell Apical Membranementioning
confidence: 97%
“…However, there is a considerable body of data showing that adipose tissue storage is not simply a matter of lipid solubility and partition. Functional groups of the drug molecules play a decisive role and basic lipophilic drugs such as haloperidol and chlorpromazine are not redistributed into adipose tissue (Betschart et al 1988;Bickel 1984;Moor et al 1992). Therefore, adipose tissue may play a role only if these drugs were stored in the adipose tissue at the site of injection as observed by Betschart et al(l988) when they administered basic lipophilic drugs by the intraperitoneal route.…”
Section: Discussionmentioning
confidence: 99%